HUMAN RIGHTS IN CONTEXT OF THE HISTORICAL NON-ALIGNED COUNTRIES’ DEBATES ON UNIVERSALISM AND CULTURAL RELATIVISM, AND CURRENT HUMAN RIGHTS DEVELOPMENT IN INDONESIA - Arinanto, Satya (Indonesian Journal of International Law, 2021)
Human rights issue was born as a result from Nazi Era by the occurrence of Universal Declaration of Human Rights in 1948. Human rights are meant to be universal by definition. The non-aligned countries generally consider human rights as western concept. The writer in this article is questioned whether or not other cultures have a concept of human rights. If they have a certain concept of human rights, the next question is whether or not it resembles that of the Universal Declaration. The writer finds it still difficult to build a bridge between universality and relativity of human rights concepts. Finally, the writer concludes that cultural relativity is real and an undeniable fact.